Contributions of leaf distribution and leaf functions to photosynthesis and water-use efficiency from leaf to canopy in apple: A comparison of interstocks and cultivars - Zhang, Xiaoyun; Yang, Weiwei; Tahir, Muhammad Mobeen; Chen, Xilong; Saudreau, Marc; Zhang, Dong; Costes, Evelyne (Frontiers in Plant Science, 2023)
Grafting has been widely used in horticulture to induce dwarfing and avoid stress-derived limitations on plant growth and yield by affecting plant architecture and leaf functions. However, the respective effects on plant photosynthesis and water use efficiency (WUE) of leaf distribution and functions that depend on both rootstock and scion have not been fully elucidated. This study aimed to (i) clarify the scion × interstock impacts on the variability of leaf photosynthetic traits and WUE, and (ii) decipher the respective effects of leaf distribution and functions on canopy photosynthesis and WUE (WUEc). Leaf gas exchange over light gradients and responses to light, CO2, temperature, and vapor pressure deficit were measured in two apple cultivars, ‘Liquan Fuji’ (‘Fuji’) and ‘Regal Gala’ (‘Gala’), grafted onto rootstocks combined with interstocks: a vigorous (VV, ‘Qinguan’), or a dwarf one (VD, M26). The 3D architecture-based RATP model was parameterized to estimate the canopy photosynthesis rate (Ac), transpiration rate (Ec), and WUEc. Then, virtual scenarios were used to compare the relative contributions of cultivar and interstock to canopy Ac, Ec, and WUEc. These scenarios changed the leaf distribution and functions of either cultivar or interstock. At the leaf scale, VD trees had significantly higher leaf nitrogen per area but a lower maximum carboxylation rate and dark respiration in both cultivars. In parallel with higher leaf stomatal conductance (gs) and transpiration in VD ‘Fuji’ and similar gs in VD ‘Gala’, VD trees showed significantly lower leaf photosynthesis rate and WUE than VV trees. However, lower leaf photosynthetic capacities in VD trees were compensated at the canopy scale, with Ac and WUEc for ‘Fuji’ significantly improved in VD trees under both sunny and cloudy conditions, and for ‘Gala’ significantly improved in VD trees under cloudy conditions compared with VV trees. Switching scenarios highlighted that ‘Gala’ leaf functions and distribution and VD leaf distributions enhanced Ac and WUEc simultaneously, irrespective of weather conditions. Up-scaling leaf gas exchange to the canopy scale by utilizing 3D architecture-based modeling and reliable measurements of tree architecture and leaf functional traits provides insights to explore the influence of genetic materials and tree management practices.